Student-Centered Assessment - Contentions, Reticence and the Way Forward - Abdullah, Ayesha S. (Pakistan Armed Forces Medical Journal, 2025)
There is probably more bad practice and ignorance of significant issues in the area of assessment than in any other aspect of higher education. This would not be so bad if it were not for the fact that the effects of bad practice are far more potent than they are for any aspect of teaching. Students can, with difficulty, escape from the effects of poor teaching, they cannot (by definition if they want to graduate) escape the effects of poor assessment”. 1 The last hundred years have witnessed milestone developments in the domain of curriculum development and teaching - learning in medical education The focus of medical education has shifted from the teacher-centeredness to student-centeredness. However, this focus has yet to include assessment practices. Assessment has always been and will remain to be the most critical component of medical education in terms of its impact on the student, the system of education and the regulatory requirements. Learning, being the central outcome of any educational programme, is the main purpose of all educational interventions. Assessment not only authenticates, quantifies and certifies learning but it also evaluates the teachers, educational programme, the systems that are designed to actualize learning and the impact of learning. Therefore, if assessment is not focused on learning it loses its purpose. There is no doubt that assessment drives learning but if it does not follow the purpose for which it was designed, it can disrupt learning with lifelong consequences for the student, the system and the end-user of health care– the patient. 2